2019
DOI: 10.1111/exd.13940
|View full text |Cite
|
Sign up to set email alerts
|

Platelets are important for the development of immune tolerance: Possible involvement of TGF‐β in the mechanism

Abstract: Platelets have diverse roles in immune processes in addition to their key functions in haemostasis and thrombosis. Some studies imply that platelets may be possibly related to the immune tolerance induction. However, the role of platelets in the development of immune tolerance is not fully understood. The purpose of this study was to investigate the role of platelets in the development of regulatory mechanisms responsible for cutaneous inflammation using a mouse model of low zone tolerance (LZT). Mice were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Although GVHD has been linked to accelerated platelet destruction [23][24][25] and decreased production, platelets have been shown to be important for the induction of immune tolerance and regulatory T-cell function either directly through cell-cell interactions or via release of transforming growth factor-B1. 23,26 Furthermore, persistent thrombocytopenia after allo-HCT has been found to be a strong negative predictor of survival independent of GVHD, 27 which is not surprising given that many common contributors to NRM, such as sepsis, thrombotic microangiopathy, veno-occlusive disease/sinusoidal obstruction syndrome, and so on, involve endothelial damage and platelet consumption or destruction. Finally, thrombocytopenia is likely also associated with NRM through endothelium-independent mechanisms; given the high incidence of infectious-related deaths in our cohorts, viral infection and their therapies may have been confounders contributing to the association of high EASIX with NRM.…”
Section: Discussionmentioning
confidence: 99%
“…Although GVHD has been linked to accelerated platelet destruction [23][24][25] and decreased production, platelets have been shown to be important for the induction of immune tolerance and regulatory T-cell function either directly through cell-cell interactions or via release of transforming growth factor-B1. 23,26 Furthermore, persistent thrombocytopenia after allo-HCT has been found to be a strong negative predictor of survival independent of GVHD, 27 which is not surprising given that many common contributors to NRM, such as sepsis, thrombotic microangiopathy, veno-occlusive disease/sinusoidal obstruction syndrome, and so on, involve endothelial damage and platelet consumption or destruction. Finally, thrombocytopenia is likely also associated with NRM through endothelium-independent mechanisms; given the high incidence of infectious-related deaths in our cohorts, viral infection and their therapies may have been confounders contributing to the association of high EASIX with NRM.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in sepsis mouse models have shown that blocking the P2Y12 receptor with clopidogrel alleviates TGF-β elevation in the plasma and restrains Treg population growth in the spleen during sepsis [145]. Using an immune tolerance mouse model, Hotta et al [147] have shown that platelet depletion reverses the increase in Tregs in the inflamed skin and draining lymph nodes of mice via TGF-β release, and significantly enhances the contact hypersensitivity response tolerance of cutaneous inflammation. Furthermore, in a recent study, platelets have been observed to recruit neutrophils into the lungs during the onset of bacterial-induced pneumonia, and to recruit Tregs and transcriptionally reprogrammed alveolar macrophages to an anti-inflammatory phenotype during the resolution phase.…”
Section: Platelet-leukocyte Interactions Orchestrating the Resolution...mentioning
confidence: 86%
“…Wound healing is a long and complex process and begins with hemostasis (hemostasis phase). Platelets release many factors, including transforming growth factor-β1 (TGFβ1), which induces inflammatory cell migration (22). These inflammatory cells produce various cytokines (23).…”
Section: Discussionmentioning
confidence: 99%